Evaluation on the tribological properties of palm olein in different loads applied using pin-on-disk tribotester - N. Sapawe (Jurnal Tribologi, 2014)
The vegetable oil based lubricant as lubricant in various applications were intensified and eyed by the industry due to its superior tribological properties, and has potential to replace petroleum based lubricants. Palm olein could be suitable and attractive candidate as the lubricant to be studied due to its good advantages and large production in country. Thus, in the study the behavior of RBD palm olein characteristic was investigated by pin on disk experiment in which the hemispherical pin was loaded against the rotating grooved disk. The experiments by sliding were performed in pin on disk tester using titanium as material for both hemispherical pin and grooved disk. The test were implemented by dropping 5 ml of RBD palm olein as lubricating oil on sliding surface at different loads applied which were 5N, 20N, 40N and 80N. The wear rate of the pin and friction coefficient was also investigated. The weight loss and surface roughness before and after experiment were analyzed. All the results obtained were compared to hydraulic oil and paraffinic mineral oil. From the analysis, friction coefficient acquired lubricated with RBD palm olein was the lowest for both conditions. Wear rate obtained for three lubricants increased from 5N to 20N load, then decreased after 40N load and increased again after 80N load exerted. Wear obtained lubricated with hydraulic oil shows the lowest value compared to paraffinic mineral oil and RBD palm olein.